Maternal chronic hypoxia increases expression of genes regulating lung liquid movement and surfactant maturation in male fetuses in late gestation. (7th May 2017) - McGillick, Erin V.; Orgeig, Sandra; Allison, Beth J.; Brain, Kirsty L.; Niu, Youguo; Itani, Nozomi; Skeffington, Katie L.; Kane, Andrew D.; Herrera, Emilio A.; Giussani, Dino A.; Morrison, Janna L.
Abstract : Key points: Chronic fetal hypoxaemia is a common pregnancy complication associated with intrauterine growth restriction that may influence respiratory outcome at birth. We investigated the effect of maternal chronic hypoxia for a month in late gestation on signalling pathways regulating fetal lung maturation and the transition to air‐breathing at birth using isobaric hypoxic chambers without alterations to maternal food intake. Maternal chronic hypoxia in late gestation increases fetal lung expression of genes regulating hypoxia signalling, lung liquid reabsorption and surfactant maturation, which may be an adaptive response in preparation for the successful transition to air‐breathing at birth. In contrast to other models of chronic fetal hypoxaemia, late gestation onset fetal hypoxaemia promotes molecular regulation of fetal lung maturation. This suggests a differential effect of timing and duration of fetal chronic hypoxaemia on fetal lung maturation, which supports the heterogeneity observed in respiratory outcomes in newborns following exposure to chronic hypoxaemia in utero . Abstract: Chronic fetal hypoxaemia is a common pregnancy complication that may arise from maternal, placental and/or fetal factors. Respiratory outcome of the infant at birth likely depends on the duration, timing and severity of the hypoxaemic insult. We have isolated the effect of maternal chronic hypoxia (MCH) for a month in late gestation on fetal lung development. Pregnant ewes were exposed to normoxia (21% O2 ) or hypoxia (10% O2 ) from 105 to 138 days of gestation (term ∼145 days). At 138 days, gene expression in fetal lung tissue was determined by quantitative RT‐PCR. Cortisol concentrations were determined in fetal plasma and lung tissue. Numerical density of surfactant protein positive cells was determined by immunohistochemistry. MCH reduced maternal P a O 2 (106 ± 2.9  vs . 47 ± 2.8 mmHg) and fetal body weight (4.0 ± 0.4  vs . 3.2 ± 0.9 kg). MCH increased fetal lung expression of the anti‐oxidant marker CAT and decreased expression of the pro‐oxidant marker NOX‐4 . MCH increased expression of genes regulating hypoxia signalling and feedback ( HIF‐3α, KDM3A, SLC2A1, EGLN‐3 ). There was no effect of MCH on fetal plasma/lung tissue cortisol concentrations, nor genes regulating glucocorticoid signalling ( HSD11B‐1, HSD11B‐2, NR3C1, NR3C2 ). MCH increased expression of genes regulating sodium ( SCNN1‐B, ATP1‐A1, ATP1‐B1 ) and water ( AQP‐4 ) movement in the fetal lung. MCH promoted surfactant maturation ( SFTP‐B, SFTP‐D, ABCA3 ) at the molecular level, but did not alter the numerical density of surfactant positive cells in lung tissue. MCH in late gestation promotes molecular maturation of the fetal lung, which may be an adaptive response in preparation for the successful transition to air‐breathing at birth. Key points: Chronic fetal hypoxaemia is a common pregnancy complication associated with intrauterine growth restriction that may influence respiratory outcome at birth. We investigated the effect of maternal chronic hypoxia for a month in late gestation on signalling pathways regulating fetal lung maturation and the transition to air‐breathing at birth using isobaric hypoxic chambers without alterations to maternal food intake. Maternal chronic hypoxia in late gestation increases fetal lung expression of genes regulating hypoxia signalling, lung liquid reabsorption and surfactant maturation, which may be an adaptive response in preparation for the successful transition to air‐breathing at birth. In contrast to other models of chronic fetal hypoxaemia, late gestation onset fetal hypoxaemia promotes molecular regulation of fetal lung maturation. This suggests a differential effect of timing and duration of fetal chronic hypoxaemia on fetal lung maturation, which supports the heterogeneity observed in respiratory outcomes in newborns following exposure to chronic hypoxaemia in utero .